Gyltors anpassningsförmåga till nya miljöer - Hellsten, Ida (2020)
Since 1988, Sweden has had legal requirements to keep gestation sows group-housed. In 2012 there was a switch in the Swedish breeding material ant the Dutch Yorkshire (DY) was introduced to the Swedish producers, a breed that has been kept in individual stalls in comparison to the Swedish breeds, like Swedish Yorkshire (SY) that DY replaced. Previous studies have found that different social treatments of pigs and piglets in general have had a significant difference, for instance, on regrouping and weaning. The aim of this study was to find if there are any difference between the breeds SY and DY in the gilt’s response to isolation just before the first farrowing. It was also studied whether or not different social environments during the gilts’ early and late growth affected the gilts’ response to isolation. A total of 93 gilts were used in this study, 39 SY and 49 DY. The gilts experienced their first social treatment (during nursing period) when they were two weeks old and this lasted until they reached an age of five weeks. The treatment involved the piglets living in loose farrowing pens, either in an “Access pen” or in a “Closed pen”. Piglets living in an “Access pen” had the opportunity to access the neighbouring pen and interact with the sow and piglets there. Piglets living in “Closed pen” did not have access to the neighbouring pen. The second social treatment was executed when the gilts were ten weeks old. This treatment involved being regrouped into a group of four gilts, either in a constellation of only littermates or in a group consisting of two gilts from two different litters. These groups remained intact, and the gilts were inseminated at approximately 25 weeks of age and separated from their group of four a week before expected farrowing and moved to individual farrowing pens. In connection with this separation, an isolation test was performed. The isolation test was done by noting the time it took for each gilt to lie down the first time. The data from the isolation test were analysed by variance analysis (General linear model). No significant results were found for neither the first social treatment (p=0.442) or the second social treatment (p=0.562). Different social treatments might therefore not have impact on the gilts facing social isolation in the farrowing pen. A significant difference between the breeds SY and DY was found (p=0.005), it took longer time for the SY-gilts to lie down in the farrowing pen compared with the DY-gilts. This could indicate that the DY-gilts have been indirectly selected to manage individual stalls. In conclusion, breed seems to affect when the gilt settles after moving to the farrowing pen. However, more research is needed in order to obtain a deeper understanding regarding the importance of social environments and breeds in concerns to how well suited they are for group housing. Keywords: pig, gilt, genotype, isolation, social treatment